Re-examining power and privilege in collective impact. Issue 2 (14th March 2016) - LeChasseur, Kimberly
Abstract: The dual purpose of this article is to deconstruct the collective impact approach's treatment of power and privilege while reconstructing the model's potential to encourage equity agendas in community change. Drawing on discourse analysis of three articles describing collective impact and case studies of two equity-oriented partnerships, analyses explore entry points for framing collective impact in ways that encourage equity as a foundation to partnership practices. Analyses suggest that the original descriptions of the approach referenced by community partners promote the marketization of change and a universal view of success, which mask opportunities to draw on the strengths of individuals and address the distribution of resources. However, partners in two communities in the US were able to use shared measurement practices to layer equity agendas onto the approach. Partners in these cases went beyond the guidance provided through the collective impact approach's tenets at the advice of funders and community partners.